Islamic Values in Lecturer Competency Development: A Systematic Literature Review of Trends, Frameworks, and Impacts in Islamic Higher Education - Orgianus, Yan; Oemar, Hirawati; Praseytaningsih, Endang; Khairo Amalia, Hani (Jurnal Pendidikan Islam, 2024)
Purpose – This study examines the integration of Islamic values into lecturer competencies in Islamic higher education, addressing how principles such as sidq (honesty), amanah (trustworthiness), and al-mas’ūliyyah (responsibility) enhance professional teaching practices and educational outcomes. It aims to propose a value-based competency framework for holistic lecturer development. Design/methods/approach – A systematic literature review (SLR) was conducted on 16 peer-reviewed studies published between 2016 and 2023, retrieved from the Scopus database using key terms "Islamic AND lecturer AND competence." Content analysis was employed to identify themes and patterns in the integration of Islamic values into professional, pedagogical, and personal competencies. Findings – The review highlights five key competency dimensions: professional, pedagogical, personal, social, and ethical. Integrating Islamic values improves teaching quality, ethical education, and student learning outcomes. Research trends show increasing interest from 2016 to 2022, emphasizing diverse methodologies such as case studies, qualitative approaches, and statistical models. Research implications – The study proposes embedding Islamic values in professional development programs, incorporating ethical indicators into performance evaluations, and adopting inclusive, value-driven pedagogical strategies to enhance educational excellence in Islamic higher education